The Relationship Between Concentration and Volleyball Serve Accuracy Among Junior High School Extracurricular Participants - Dzira Alfikri Islami; Taufiq Hidayah (Universitas Negeri Semarang, 2026)
This study aimed to determine the relationship between concentration and volleyball service accuracy among junior high school extracurricular participants. This research employed a quantitative approach with a correlational design. The sample consisted of 20 students participating in volleyball extracurricular activities. The instruments used were a concentration test and a volleyball service accuracy test. Data were analyzed using normality tests, linearity tests, and Pearson Product Moment correlation analysis. The results showed a significant relationship between concentration and volleyball service accuracy (r = 0.650; p = 0.002 < 0.05). These findings indicate that higher levels of concentration are associated with better service accuracy. Therefore, concentration is one of the psychological factors contributing to the successful execution of volleyball service techniques.